2021
DOI: 10.1083/jcb.202103003
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic expansion of hepatocyte lumina enforced by apical bulkheads

Abstract: Lumen morphogenesis results from the interplay between molecular pathways and mechanical forces. In several organs, epithelial cells share their apical surfaces to form a tubular lumen. In the liver, however, hepatocytes share the apical surface only between adjacent cells and form narrow lumina that grow anisotropically, generating a 3D network of bile canaliculi (BC). Here, by studying lumenogenesis in differentiating mouse hepatoblasts in vitro, we discovered that adjacent hepatocytes assemble a pattern of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 86 publications
(120 reference statements)
5
43
0
Order By: Relevance
“…During hepatoblast-to-hepatocyte differentiation in the developing liver, adjacent hepatoblasts initially form small spherical lumina between their apical membranes. These apical lumina then expand anisotropically, generating narrow tubules that ultimately connect to complete the formation of the BC network ( Belicova et al, 2021 ). Similar to lumen expansion in other epithelia, BC elongation is driven by secretion of ions (bile acids and other organic solutes) into the nascent lumen ( Boyer, 2013 ; Bryant and Mostov, 2008 ; Dasgupta et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During hepatoblast-to-hepatocyte differentiation in the developing liver, adjacent hepatoblasts initially form small spherical lumina between their apical membranes. These apical lumina then expand anisotropically, generating narrow tubules that ultimately connect to complete the formation of the BC network ( Belicova et al, 2021 ). Similar to lumen expansion in other epithelia, BC elongation is driven by secretion of ions (bile acids and other organic solutes) into the nascent lumen ( Boyer, 2013 ; Bryant and Mostov, 2008 ; Dasgupta et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve anisotropic expansion of the apical lumen, hepatocytes need to balance the isotropic hydrostatic pressure in the lumen with anisotropic forces in the subapical actomyosin cortex ( Li et al, 2016 ). We recently reported that BC elongation is enforced by apical bulkheads, F-actin–containing extensions of the apical membrane that traverse the canalicular lumen and connect juxtaposed hepatocytes ( Belicova et al, 2021 ). The structure of apical bulkheads and their role in BC formation suggest that they are mechanical elements that generate anisotropy in the subapical actomyosin cortex, thereby driving BC elongation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro cell culture assays have been used to identify regulators of lumen establishment or ciliogenesis and have identified 3 potential Rab GTPases that are involved in both: Rab11, Rab8, and Rab35 [18][19][20][21][22][23][24]. Here we investigated the role of these three Rab GTPases in KV development.…”
Section: Introductionmentioning
confidence: 99%
“…Several pathways have been proposed to play key roles in BC morphogenesis such as mitosis, cytokinesis and endosomal trafficking ( 4 , 5 , 6 ), nevertheless the mechanistic studies are lacking. Belicova and colleagues set out to investigate the basic mechanisms for BC formation ( 7 ).…”
mentioning
confidence: 99%